Business environment, training, human resources development and entrepreneurial readiness for employees of PT Industri Telekomunikasi Indonesia - Kosasih Kosasih (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This research aims to determine the effect of the business environment, training, and human resource development on the entrepreneurial readiness of employees of PT Industri Telekomunikasi Indonesia.  The research method used is descriptive quantitative. The data of this study is primary data, namely the data from questionnaires distributed to respondents. The population in this study were all employees of PT Industri Telekomunikasi Indonesia in the position of April 2021 as many as 276 people, and the sample was taken using a random sampling method with a total of 57 respondents. The method of analysis and testing of research data used is modeling using the Amos 24.0 program while verification testing with an approach in modeling and solution techniques that will be used as an analysis tool Modeling on variants or components, namely PLS (Partial Least Square). The resulting study is shown that there is a positive influence of the business environment on readiness for entrepreneurship, the positive effect of training on readiness for entrepreneurship, and a positive effect on human resource development on readiness for entrepreneurship.